KLF7-IT1-ARPC2 axis in macrophages orchestrates caspase-4-driven hypercoagulation in sepsis - Wang, Xiangyu; Lu, Yanyan; Yuan, Chuang; Yang, Xinyu (Biochemical and biophysical research communications, 2025)
Sepsis is characterized by dysregulated inflammation and coagulation leading to organ dysfunction, yet the molecular mechanisms linking these processes remain elusive. Through transcriptomic profiling of leukocytes from septic and non-septic patients, we identified Kruppel-like factor 7 intronic transcript 1 (KLF7-IT1) as one of the most robustly upregulated long non-coding RNAs in sepsis. Elevated KLF7-IT1 expression correlated strongly with hypercoagulability, inflammatory cytokines, and multi-organ injury, suggesting a pathogenic role in septic coagulopathy. Functional studies revealed that KLF7-IT1 promotes macrophage procoagulant activity by enhancing caspase-4 activation and gasdermin-D–mediated pyroptosis, leading to increased phosphatidylserine exposure and tissue factor activity. Mechanistically, KLF7-IT1 stabilized actin-related protein 2/3 complex subunit 2 (ARPC2), a core subunit of the Arp2/3 complex essential for actin remodeling, thereby facilitating intracellular LPS internalization and downstream caspase-4 activation. Silencing ARPC2 markedly attenuated these effects, revealing a novel cytoskeletal mechanism connecting endotoxin sensing to pyroptotic cell death. Furthermore, KLF7-IT1 amplified macrophage–neutrophil cross-talk, where macrophage pyroptosis induced neutrophil extracellular trap (NET) formation, reinforcing thrombo-inflammation and coagulation. Collectively, these findings identify KLF7-IT1 as a pivotal regulator that integrates cytoskeletal remodeling, pyroptosis, and NETosis into a unified procoagulant network in sepsis. Targeting the KLF7-IT1-ARPC2-caspase-4 axis may provide a novel therapeutic strategy to disrupt the vicious cycle of inflammation-driven coagulation and mitigate sepsis-associated organ failure. •KLF7-IT1 is highly associated coagulation and organ dysfunction in sepsis.•KLF7-IT1 drives coagulation via caspase-4/GSDMD-augmented tissue factor activity and pyroptotic macrophage-induced NETosis.•KLF7-IT1 stabilizes ARPC2 to facilitate LPS internalization, linking actin remodeling to caspase-4/GSDMD-dependent pyroptosis.